Programming Languages and Systems 21st European Symposium on Programming, ESOP 2012, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2012, Tallinn, Estonia, March 24 - April 1, 2012. Proceedings - Seidl, Helmut; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 21st European Symposium on Programming, ESOP 2012, held in Tallinn, Estonia, as part of ETAPS 2012, in March/April 2012. The 28 full papers, presented together with one full length invited talk, were carefully reviewed and selected from 92 submissions. Papers were invited on all aspects of programming language research, including: programming paradigms and styles, methods and tools to write and specify programs and languages, methods and tools for reasoning about programs, methods and tools for implementation, and concurrency and distribution.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Computer Communication Networks; Logics and Meanings of Programs; Programming Techniques; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages